Heterotrophic carbon dioxide fixation by Euglena - Peak, Jennifer Grace (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1978)
Heterotrophic (dark, non-photosynthetic) carbon dioxide fixation was measured in the phytoflagellate Euglena gracilis. Variation in heterotrophic carbon dioxide fixation depends on the phase of batch growth and the mode of nutrition. A sharp increase in heterotrophic carbon dioxide fixation occurs during the mid- to late-logarithmic growth periods in Euglena growing photoautotrophically (with carbon dioxide as carbon source, light as energy source) and heterotrophically (in the dark with glucose as sole carbon and energy source). Cells growing heterotrophically with acetate or ethanol as sole carbon source do not increase their heterotrophic carbon dioxide fixation during the growth cycle. Addition of acetate to cultures of Euglena causes a reduction in dark carbon dioxide fixation. The results are consistent with the hypothesis that heterotrophic carbon dioxide fixation in Euglena functions in anaplerotic replenishment of the tricarboxylic acid cycle. The regulation of these changes in heterotrophic carbon dioxide fixation was shown to be controlled by exogenous ammonium in a complex fashion. Ammonium stimulates heterotrophic carbon dioxide fixation after a period of ammonium deprivation. The kinetics of the regulatory effects of the ammonium ion on dark carbon dioxide fixation are presented. A survey into the activities of carboxylating enzymes from both autotrophically and heterotrophically grown Euglena was conducted. The heterotrophic cultures were supplied with either glucose or acetate as substrate. PEP carboxykinase (E.C.4.1.1.38) and (E.C.4.1.1.49) could not be detected in any of the cultures tested. A trace amount of PEP carboxykinase (E.C.4.1.1.32) is present in the acetate grown cells only and a trace amount of pyruvate carboxylase (E.C.6.4.1.1.) is present in the glucose grown cells only. Malate enzyme (E.C.1.1.1.40), PEP carboxylase (E.C.4.1.1.31) and acetylcoenzyme A carboxylase (E.C.6.4.1.2) are present in all cells tested. Ammonium stimulation causes a small increase in specific activity of all the enzymes except acetyl-CoA carboxylase. The largest increase occurs in PEP carboxylase, but the increase is not sufficient to account for observed increases in whole cell dark carbon dioxide fixation after ammonium stimulation. Two isoenzymes of PEP carboxylase were purified from each other from both ammonium stimulated and non-stimulated cells. There are no significant differences between elution profiles of isoenzymes from ammonium stimulated and control cells. There are no significant differences between elution profiles of isoenzymes from autotrophic and heterotrophic cells. The kinetics of the regulation of the two isoenzymes by malate, citrate, succinate and 3-phosphoglycerate are presented. The products of heterotrophic carbon dioxide fixation by ammonium stimulated and control cells were identified and measured by chromatography. Ammonium stimulates the biosynthesis of glutamine, glycine, serine and alanine.
Keywords: Euglena